The commodification of polygamy through the ecranization of the novel Air Mata Tuhan into the film Air Mata Surga - Karkono, Karkono (citeus, 2022)
This study explored the commodification of polygamy in the Air Mata Surga (AMS) movie, adapted from the Air Mata Tuhan novel. The movie was selected for a number of reasons. Firstly, it is an effective transformation medium to reach people with distinctive backgrounds, including their age, social status, domicile, education, culture, language, and even religion. Secondly, polygamy is considered sacred as it is correlated with religion. However, in the industrial sector, polygamy becomes a profane commodity once it is taken as a theme in a movie. Therefore, this study investigated the commodification types of polygamy in the AMS movie and society’s reception of those commodification. The researcher used the observation technique on material objects in a novel and film and also created a questionnaire using Google Form. The research participants came from Malang, Surakarta, and Jakarta, Indonesia. The results show that the commodification observed in the AMS movies consists of both content and audience commodification. Meanwhile, polygamy was used by the production house as a means to gain revenue and to transform ideology, both in the novel and in the movie. The findings also suggest that 78 percent of participants mentioned that their viewpoint toward polygamy shifted after watching the movie.